The technical efficiency of military industrial enterprises: A civil–military integration perspective - Li Mingxing; Oswin A. Anaba; Ma Zhiqiang; Keyi Guan; Mengjuan Zhang; Liu Xiaonan; Sun Hongzheng (South African Journal of Business Management, 2019)
Background: This article takes a look at the technical efficiency of 53 A-share listed companies of Chinese military industrial enterprises in the `10 Major Military-industrial Groups' based on the random Frontier B95 model and the panel data of listed companies from 2010 to 2015.Objectives: The research put forward five influencing factors, namely ownership structure, asset turnover, enterprise size, staff education and regional differences.Method: The article proposed five hypotheses to measure the technical efficiency of the military and civilian enterprises.Results: The results showed a gradual increase in the technical efficiency of sampled military industrial enterprises, even though the overall results were low with a decreasing scale income. There was a positive correlation between ownership concentration and the technical efficiency of military industrial enterprises, but not significant. However, the proportion of state-owned large shareholders and the technical efficiency of military industrial enterprises had a negative correlation and were not significant. Asset turnover ratio, firm size, employee education level and regional differences correlated positively with the technical efficiency of military industrial enterprises, and their influence was seen to be very important.Conclusion: The conclusion of the study provides an empirical basis for further studies enhancing the technical efficiency of military industrial enterprises in China.
Keywords: 650